1988
DOI: 10.1152/jappl.1988.64.2.789
|View full text |Cite
|
Sign up to set email alerts
|

Upper airway pressure-flow relationships in obstructive sleep apnea

Abstract: We examined the pressure-flow relationships in patients with obstructive sleep apnea utilizing the concepts of a Starling resistor. In six patients with obstructive sleep apnea, we applied incremental levels of positive pressure through a nasal mask during non-rapid-eye-movement sleep. A positive critical opening pressure (Pcrit) of 3.3 +/- 3.3 (SD) cmH2O was demonstrated. As nasal pressure was raised above Pcrit, inspiratory airflow increased in proportion to the level of positive pressure applied until apnea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
243
0
6

Year Published

1995
1995
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 391 publications
(260 citation statements)
references
References 0 publications
10
243
0
6
Order By: Relevance
“…In early studies, upper airway collapsibility during sleep was found to vary along a continuum from health to disease (54)(55)(56). The severity of upper airway obstruction during sleep is related to quantitative differences in pharyngeal collapsibility, as reflected by elevations in the critical closing pressure (Pcrit).…”
Section: Obesity and Upper Airway Neuromechanical Control Modeling Upmentioning
confidence: 99%
See 1 more Smart Citation
“…In early studies, upper airway collapsibility during sleep was found to vary along a continuum from health to disease (54)(55)(56). The severity of upper airway obstruction during sleep is related to quantitative differences in pharyngeal collapsibility, as reflected by elevations in the critical closing pressure (Pcrit).…”
Section: Obesity and Upper Airway Neuromechanical Control Modeling Upmentioning
confidence: 99%
“…These responses can restore airway patency by recruiting muscles that dilate and elongate the airway (63,65,66,67,(78)(79)(80)(81)(82)(83)(84). In patients with sleep apnea, impaired neural responses to airway obstruction account for the marked elevation in Pcrit during sleep compared with normal individuals (54)(55)(56). A disturbance in neuromuscular control is further suggested by comparisons of critical pressures measured during sleep (54-56) with those assessed in paralyzed, anesthetized subjects (69,85).…”
Section: Obesity and Upper Airway Neuromechanical Control Modeling Upmentioning
confidence: 99%
“…This has been reported in healthy subjects [12], as well as in heavy snorers [2] and OSA patients [2,13]. Inspiratory flow limitation during quiet breathing and snoring has been found in apnoeic and nonapnoeic snorers during sleep [2,13]. These changes have been attributed to a sleep-related decrease in muscle tone resulting in reduction of the crosssectional area of UA.…”
Section: Discussionmentioning
confidence: 68%
“…In fact, it was believed that ON-CPAP would not work in patients with OSA. 5,6 However, in 1994 two papers were published asserting that ON masks might be an acceptable treatment alternative for OSA. The first paper was authored by Glen Prosise and myself 7 and the second a few months later by Sanders and coworkers.…”
Section: Two Articlesmentioning
confidence: 99%